Experimental study on the pullout behavior of geogrid embedded in xanthan gum biopolymer-treated sand layers - Kim, Gi Yun; Lee, Hwijae; Kim, Junghoon; Park, Suhyuk; Yun, Tae Sup; Chang, Ilhan (Geomechanics and Engineering, 2025)
Geogrid pullout is a critical failure mode in mechanically stabilized earth (MSE) walls and must be thoroughly assessed to ensure stability. Pullout resistance consists of skin friction between the soil and geogrid and bearing (passive) resistance generated by the transverse ribs. Due to the nonlinear and complex soil–geogrid interactions, pullout tests are recommended by design and construction guidelines. This study examined the potential of encapsulating geogrids within a biopolymer-based soil treatment (BPST) layer to enhance pullout resistance. Laboratory pullout tests, conducted using an independently developed apparatus, assessed geogrid performance encapsulated in xanthan gum biopolymer hydrogel under initial (wet) and dehydration (dry) conditions across varying normal pressure levels. Results showed that under the initial (wet) condition, pullout resistance increased by at least 10% at low normal pressure levels (≤50 kPa) due to improved adhesion. Under dehydration (dry) conditions, pullout resistance significantly increased, exceeding the geogrid's tensile strength at low normal pressure levels (25 kPa), attributed to enhanced bonding and particle–geogrid interlocking. The apparent friction coefficient and interaction coefficient ratio (ICR) were introduced as metrics to evaluate pullout resistance performance. The BPST method proved effective in addressing challenges where compaction is unsuitable, reinforcement length is constrained in narrow backfill areas, or fine-grained soils are required. This eco-friendly method provides a sustainable alternative for MSE wall applications, offering improved mechanical performance and versatility.
Keywords: Biopolymer-based soil treatment; Geogrids; Mechanically stabilized earth wall; Normal pressure; Pressure level; Pull-out test; Pullout resistance; Soil treatments; Soil-geogrid interaction; Biopolymer-based soil treatment (BPST); geogrid; pullout resistance; soil-geogrid interaction